Examination of the relationship between authentic assessment and generic competencies among undergraduate science student-teachers in Tanzanian universities (Educational Dimension, 2024)
This paper investigates the relationship between authentic assessment tools and the acquisition of generic competencies among undergraduate science student-teachers in Tanzanian universities. Employing a quantitative research approach, data were gathered through questionnaires and document reviews. A sample of 231 undergraduate science student-teachers was selected using stratified proportional random sampling. The collected data underwent analysis using a multiple linear regression model. Results revealed a significant relationship between authentic assessment tools and generic competencies, with variations in generic competencies accounting for 50 per cent of the variations in authentic assessment tools. The study underscores the necessity of establishing an authentic assessment policy within universities to ensure its comprehensive implementation.